Valores de referência e reprodutibilidade para o teste de caminhada de seis minutos em crianças e adolescentes obesos - Diniz, Welton Alves (2020)
Introduction: The 6-minute walk test (6MWT) is frequently used to determine the functional capacity of several populations. However, there are no reference values nor equations for prediction for the 6MWT in Brazilian overweight and obese children and teenagers. Objectives: To propose a reference equation, as well as determine normal values for the 6MWT in Brazilian overweight and obese children and teenagers, secondarily assess IF the test is reproducible in this population and compare the performance on the 6MWT between children and teenagers. Method: This is a cross-sectional study performed with 222 children and teenagers (112 boys and 110 girls) aged six to seventeen years. The volunteers performed spirometry and measured the length of lower limb, abdominal circumference (AC), height, weight, body/mass index (BMI) and 6MWT. The independent variables were: age, height, weight and length of lower and the dependent variable was the distance walked at the 6-minute walk test (6MWD). Results: The multiple regression analysis determined the following equation for children of both sexes, expected 6MWD = 562,019 + (Age, years x 12,644) + (Weight, kg x 1,462) – (BMI, kg/m2 x -7,245) [R2 = 0,254; p = 0,027]. For the teenagers, the expected 6MWD = 523,120 + (length of lower limb, cm x 2,649) – (BMI kg/m2 x – 4,744) [R2 = 0,295; p = 0,004]. The average 6MWD walked by the male children was 591,3m ± 71,3m and the female children, 576,5m ± 60,3m. For the male teenagers the average 6MWD was 624,5m ± 61,0m and the female teenagers, 599,6m ± 60,9. The 6MWT came out to be reproducible, presenting an excellent intraclass correlation coefficient, for children as well as for teenagers, children ICC: 0,92 (IC95%: 0,89 – 0,94), p = 0,0001 and teenagers ICC: 0,94 (IC95%: 0,91 – 096) p = 0,0001. The male children walked shorter distances on 6MWT in comparison with teenagers of the same sex, being these 591,3m ± 71,3 versus 624,5m ± 61,0m, p = 0,01. However, there was no difference on the walked 6MWD by female children and teenagers of the same sex, 576,5m ± 63,1m versus 599,6m ± 60,9m, p = 0,05. Preliminary conclusions: It has been possible to establish the prevision equation and normality values for the 6MWT in overweight and obese children and teenagers, it has been observed that the anthropometric variables can explain the 6MWD in both sexes, in both children and teenagers. The 6MWT has been shown to be reproducible when performed on the same day, in a 30 meters corridor. We observed that the male children walked less than the teenagers of the same sex.